PERSONALIZATION OF BANKING SERVICES BASED ON OPEN SOURCE ANALYSIS VIA USE OF BIG DATA - E. Zaytseva (Вестник университета)
The banking sector is one of the most dynamically developing areas in the field of information technology. Modern big data analytics tools provide a wide range of opportunities for the collection and subsequent analysis of heterogeneous data, including personal one. The need to build a platform for personalization of the client’s offer is due to the exponential growth of information and banks’ desire to go digital. This platform will significantly increase the level of understanding of banks’ customers’ needs and personalize banking products and services properly.